EPIDIDIMIS DAN PERANNYA PADA PEMATANGAN SPERMATOZOA - Muslim Akmal; Dian Masyitah; Hafizuddin Hafizuddin; Fitriani Fitriani (Program Studi Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Almuslim, 2015)
Epididymis is the important organ in male reproductive system. Functions of epididymis are as transportation, maturation, and storage of sperm. Sperm of testikular are non-functional gamets, and only during transit through the epididymis, the sperm will become functional gamets. Synthesis and secretion of some proteins by epididymis epithelium are very important for maturation of sperm in epididymis. The objective is to know the important role of epididymis in secretion of some proteins or molecule and its function for sperm maturation. Keywords : Epididymis, spermatogenesis, protein